Bail-in expectations for European banks: Actions speak louder than words - Alexander Schäfer; Isabel Schnabel; Beatrice Weder di Mauro (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
The declared intention of policy makers is that future bank restructuring should be conducted through bail-in rather than bail-out. Over the past years there have been a few cases of European banks being restructured where creditors were bailed in. This paper exploits these events to investigate the market reactions of stock prices and credit default swap (CDS) spreads of European banks in order to gauge the extent to which it is expected that bail-in will indeed become the new regime. We find evidence of increased CDS spreads and falling stock prices most notably after the bail-in in Cyprus. However, bail-in expectations appear to depend on the sovereign's fiscal strength, i. e., reactions are stronger for banks in countries with limited fiscal space for bail-out. Moreover, actual bail-ins lead to stronger market reactions than the legal implementation of bank resolution regimes, supporting the saying that actions speak louder than words.
Keywords: G21; G28; 330; Bail-in; bank restructuring; Single Resolution Mechanism; creditor participation; event study